Aerodynamic analysis of SARS-CoV-2 in two Wuhan hospitals - Liu, Yuan; Ning, Zhi; Chen, Yu; Guo, Ming; Liu, Yingle; Gali, Nirmal Kumar; Sun, Li; Duan, Yusen; Cai, Jing; Westerdahl, Dane; Liu, Xinjin; Xu, Ke; et al. (Nature (London), 2020)
The ongoing outbreak of coronavirus disease 2019 (COVID-19) has spread rapidly on a global scale. Although it is clear that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is transmitted through human respiratory droplets and direct contact, the potential for aerosol transmission is poorly understood 1 – 3 . Here we investigated the aerodynamic nature of SARS-CoV-2 by measuring viral RNA in aerosols in different areas of two Wuhan hospitals during the outbreak of COVID-19 in February and March 2020. The concentration of SARS-CoV-2 RNA in aerosols that was detected in isolation wards and ventilated patient rooms was very low, but it was higher in the toilet areas used by the patients. Levels of airborne SARS-CoV-2 RNA in the most public areas was undetectable, except in two areas that were prone to crowding; this increase was possibly due to individuals infected with SARS-CoV-2 in the crowd. We found that some medical staff areas initially had high concentrations of viral RNA with aerosol size distributions that showed peaks in the submicrometre and/or supermicrometre regions; however, these levels were reduced to undetectable levels after implementation of rigorous sanitization procedures. Although we have not established the infectivity of the virus detected in these hospital areas, we propose that SARS-CoV-2 may have the potential to be transmitted through aerosols. Our results indicate that room ventilation, open space, sanitization of protective apparel, and proper use and disinfection of toilet areas can effectively limit the concentration of SARS-CoV-2 RNA in aerosols. Future work should explore the infectivity of aerosolized virus. Aerodynamic analysis of SARS-CoV-2 RNA in two hospitals in Wuhan indicates that SARS-CoV-2 may have the potential to be transmitted through aerosols, although the infectivity of the virus RNA was not established in this study.